Treatment of petroleum wastewater contaminated with hydrocarbons and inorganics by anoxic-aerobic sequential moving bed reactors. (15th June 2021) - Mallick, Subrat Kumar; Chakraborty, Saswati
Abstract: The present study deals with the biotransformation of virulent petroleum refinery concoction with phenol (750 mg/L), emulsified crude oil (300 mg/L), S 2− (750 mg/L), NH4 + -N (350 mg/L) and NO3 − -N (1000 mg/L) in anoxic (A1) - aerobic (A2) moving bed reactors operated in series. The efficacy of the system was analysed through measurement of pollutant concentrations, GC-MS and FTIR peaks of the influent and effluent, and biomass activity studies. The system was able to eliminate the organics and inorganics with more than 99% efficiency at 80 h HRT and 64 h cycle time. GC-MS results revealed breakage of high molecular weight organics to smaller compounds after anoxic treatment. Further treatment of anoxic effluent by aerobic biomass reduced the number of peaks in the final effluent significantly. FTIR results were in accord with the GC-MS results. Heterotrophic activity (HA) of the aerobic biomass was higher than anoxic biomass due to its higher free energy change. Anoxic biomass showed chemolithotrophic activity (CA), suggesting survival in the absence of organics. Gas generated from anoxic reactor consisted of 91% nitrogen, 1% CO2, 1% H2 S and rest was unaccounted. Graphical abstract: Image 1 Highlights: 99% efficiency of the anoxic-aerobic reactor for organics and inorganics removal. Aerobic biomass was higher compared to anoxic biomass. Alkanes and acids were dominant in influent containing crude oil. Both heterotrophic and chemolithotrophic activity shown by anoxic bacteria. Nitrogen gas was dominant from the reduction of nitrate.